2018
DOI: 10.1093/chemse/bjy038
|View full text |Cite
|
Sign up to set email alerts
|

Global Study of Social Odor Awareness

Abstract: Olfaction plays an important role in human social communication, including multiple domains in which people often rely on their sense of smell in the social context. The importance of the sense of smell and its role can however vary inter-individually and culturally. Despite the growing body of literature on differences in olfactory performance or hedonic preferences across the globe, the aspects of a given culture as well as culturally universal individual differences affecting odor awareness in human social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…For example, the rules of interpersonal distances during social interactions (theory of proxemics [106]) vary according to culture [107] and may have a role in chemical communication, as hypothesized in some cultural comparisons of body odour perception [108,109]. Cultural variations do also exist in emotional responses to odours [110,111] and in the language used to evoke odours (see [112]). Cultural variations in cosmetic and drug practices may also be influential, as detailed hereafter.…”
Section: Challenge 3: Cross-cultural Studiesmentioning
confidence: 99%
“…For example, the rules of interpersonal distances during social interactions (theory of proxemics [106]) vary according to culture [107] and may have a role in chemical communication, as hypothesized in some cultural comparisons of body odour perception [108,109]. Cultural variations do also exist in emotional responses to odours [110,111] and in the language used to evoke odours (see [112]). Cultural variations in cosmetic and drug practices may also be influential, as detailed hereafter.…”
Section: Challenge 3: Cross-cultural Studiesmentioning
confidence: 99%
“…In addition, as has been suggested elsewhere (e.g. Smeets et al 2008;Sorokowska et al 2018), it could be that individuals who rate their sense of smell as important are also more aware of odours and consequently more sensitive to the positive and negative effects of odours. Extrapolating from this evidence, it can be theorised that individuals who score higher on the IOQ may rely more heavily on their sense of smell during social situations and therefore be more emotionally affected by others' positive and negative emotions.…”
Section: Discussionmentioning
confidence: 65%
“…It was argued that the neuroanatomical convergence of olfactory and emotional brain areas was a possible explanation for this finding. Additionally, Sorokowska et al (2018) suggested that individuals paying more attention to the odours that they detected explained the evidence they found indicating the existence of individual differences in self-reported social odour awareness. This increased olfactory consideration may consequently lead to others' positive or negative olfactory chemosignals being more readily detected.…”
Section: Perceived Importance Of Olfactionmentioning
confidence: 87%
“…Varied levels of the general attitude as well as the subscale dimensions have been shown in population from different regions (55) . However, using selected items from the OAS, there is research demonstrating that the variability in odor awareness is largely due to gender, age and education, but less due to country (57) . One strength of the IOQ is the measure of different aspects of attitudes towards odors or olfaction, and inclusion of the aggravation scale to identify the overestimation of olfactory significance among clinical populations (e.g.…”
Section: Awareness and Attitude Towards Olfactionmentioning
confidence: 99%